Investigating effect of different reflective surfaces on solar thermal collector - Chua Y.L.; Chin K.K.; Tay T.T. (American Institute of Physics Inc., 2023)
This paper reports on the experiments conducted to investigate the efficiency of different type of reflecting surfaces used on solar thermal collector. Three types of commonly available reflective surfaces coated with silver colour acrylic paint, reflective aluminium foil and blank compact disc are investigated. In this paper, the effect of different reflective surfaces on the water container and parabolic concentrator dish are investigated. In the first experiment, two types of surfaces, coated with silver colour acrylic paint and black colour acrylic paint on an aluminium container are compared. The other factors that might influence the experiment outcome like the material, focal point, and weather condition are kept constant. The experiment results proved that black colour surface is better in absorbing heat reflected by the parabolic dish. The second experiment focused on investigating the effect of different reflective surfaces on the parabolic concentrator dish itself. These surfaces are tested on a parabolic disc of a static solar thermal collector that reflects heat from the sun to a body of water stored in a black colour aluminium container. The temperature of the water is measured at a predetermined interval to measure the efficiency of the reflective surfaces used. It is found that the aluminium reflective surface performed the best compared to the other surfaces. 2017 Author(s).